Mn-BiOCl-coal-based hard carbon composite material as well as preparation method and application thereof

By preparing Mn-BiOCl-based hard carbon composite material, the problem of slow diffusion of sodium ions in sodium ion batteries was solved, and efficient electrochemical performance was achieved, and the first circle of Coulomb efficiency reached 81.2%.

CN119852351APending Publication Date: 2025-04-18HUBEI UNIV OF AUTOMOTIVE TECH +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411887653.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

Due to the large sodium ion radius of sodium ion, the diffusion rate in the electrode material is relatively slow, which affects the capacity and cycling performance of sodium ion batteries.

Method used

Mn-BiOCl-coal-based hard carbon composite material was used to synthesize Mn-BiOCl powder by carbonization and hydrothermal reaction, and then mix with coal-based hard carbon material and calcined to prepare composite materials with excellent electrochemical properties.

Benefits of technology

Under the current density of 10Ag-1 and the voltage window of 0.01 to 1.5V, the first circle of Coulomb efficiency can reach 81.2%, significantly improving the electrochemical performance of sodium ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852351A_ABST
    Figure CN119852351A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery energy storage materials, and discloses a Mn-BiOC-coal-based hard carbon composite material as well as a preparation method and application thereof. The preparation method of the Mn-BiOCl-coal-based hard carbon composite material comprises the following steps: 1) under the protection of nitrogen, carrying out carbonization treatment on a coal-based material to obtain a coal-based hard carbon material; 2) adding Bi (NO3) 3.5 H2O, NaCl and manganese salt into distilled water, and stirring to obtain a mixed solution; (3) mixing the mixed solution obtained in the step (2) with a carbon precursor material, and carrying out hydrothermal reaction to obtain Mn-BiOCl powder; and 4) mixing the coal-based hard carbon material obtained in the step 1) and the Mn-BiOCl powder obtained in the step 3), and calcining to obtain the Mn-BiOCl-coal-based hard carbon composite material. According to the Mn-BiOC-coal-based hard carbon composite material provided by the invention, the first-circle coulombic efficiency can reach 81.2% under the current density of 10 Ag <-1 > and the voltage window of 0.01-1.5 V, and the Mn-BiOC-coal-based hard carbon composite material has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion battery energy storage materials, and in particular to a Mn-BiOCl-coal-based hard carbon composite material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have become a potential technology to replace lithium-ion batteries because of their similar working principles to lithium-ion batteries, abundant sodium resources and low cost. However, due to the large radius of sodium ions, the diffusion rate of sodium ions in electrode materials is relatively slow, and it is difficult to embed sodium ions into electrode materials, which seriously affects the capacity and cycle performance of sodium-ion batteries. Therefore, the development of high-performance electrode materials suitable for sodium-ion batteries, especially materials that can improve the conductivity and electrochemical reaction activity of sodium-ion batteries, has become a hot research topic in this field.

[0003] Bismuth oxychloride (BiOCl) is a layered material with unique electrochemical properties and good sodium storage performance, but its conductivity is poor and it is prone to volume expansion during the electrochemical cycle, leading to damage to the battery structure; hard carbon, as a common carbon material, has good conductivity and a high specific surface area, and can also alleviate the volume expansion problem of the material; therefore, compounding BiOCl with coal-based hard carbon to provide a sodium ion battery electrode material with superior electrochemical properties has become a technical problem that needs to be urgently solved by those skilled in the art. Summary of the invention

[0004] The purpose of the present invention is to provide a Mn-BiOCl-coal-based hard carbon composite material and a preparation method and application thereof. The Mn-BiOCl-coal-based hard carbon composite material has excellent electrochemical properties.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A method for preparing a Mn-BiOCl-coal-based hard carbon composite material comprises the following steps:

[0008] 1) Carbonizing the coal-based material under nitrogen protection to obtain a coal-based hard carbon material;

[0009] 2) Change Bi(NO 3 ) 3 ·5H 2 O, NaCl and manganese salt are added into distilled water and stirred to obtain a mixed solution;

[0010] 3) mixing the mixed solution obtained in step 2) with the carbon precursor material, and subjecting the mixture to a hydrothermal reaction to obtain Mn-BiOCl powder;

[0011] 4) The coal-based hard carbon material obtained in step 1) and the Mn-BiOCl powder obtained in step 3) are mixed and calcined to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0012] Furthermore, in step 1), before the coal-based material is carbonized, the coal-based material needs to be pretreated, specifically: the coal-based material is placed in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60°C for 6-12h, centrifuged and dried.

[0013] Furthermore, in step 1), the carbonization treatment is specifically as follows: controlling the heating rate to be 5°C / min, heating to 1200-1600°C, and high temperature calcining for 2-4h.

[0014] Further, in step 2), the manganese salt comprises: MnCl 2 , Mn 2 CO 3 , C 4 H 6 MnO 4 ·4H 2 O、MnSO 4 and Mn(NO 3 ) 2 .

[0015] Further, in step 2), the Bi(NO 3 ) 3 ·5H 2 The molar volumes of O, NaCl, manganese salt and distilled water are 3mmol:3mmol:(3-6)mmol:70mL.

[0016] Furthermore, in step 3), the mass volume of the mixed solution and the carbon precursor material is 70 mL: (0.1-0.3) g.

[0017] Furthermore, in step 3), the hydrothermal reaction is specifically: hydrothermal reaction at 160° C. for 16 hours.

[0018] Furthermore, in step 4), the mass ratio of the coal-based hard carbon material to the Mn-BiOCl powder is (1-10):1.

[0019] Furthermore, in step 4), the calcination is specifically: calcining at 500° C. for 1 to 12 hours.

[0020] The second technical solution of the present invention:

[0021] The Mn-BiOCl-coal-based hard carbon composite material is prepared by the above-mentioned preparation method of the Mn-BiOCl-coal-based hard carbon composite material.

[0022] The third technical solution of the present invention:

[0023] The use of the above-mentioned Mn-BiOCl-coal-based hard carbon composite material in preparing a sodium ion battery electrode comprises the following steps:

[0024] The Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black are dissolved in N-methylpyrrolidone to obtain an electrode slurry, and then the electrode slurry is dried and compacted to obtain the sodium ion battery electrode.

[0025] Furthermore, before preparing the sodium ion battery electrode, the Mn-BiOCl-coal-based hard carbon composite material needs to be sieved using a standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size.

[0026] Furthermore, the mass ratio of the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black is 8:1:1.

[0027] Furthermore, the drying process is specifically: drying at 60-80° C. for 12 hours.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] The Mn-BiOCl-coal-based hard carbon composite material provided by the present invention is -1 The current density is 0.01-1.5V, and the first-cycle coulombic efficiency can reach 81.2% in the voltage window, which has excellent electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. Moreover, the same reference symbols are used throughout the accompanying drawings to represent the same components. In the accompanying drawings:

[0031] Figure 1 The electrochemical performance test results of the sodium ion battery electrode prepared in Application Example 1;

[0032] Figure 2 The electrochemical performance test results of the sodium ion battery electrode prepared in Application Example 2;

[0033] Figure 3The electrochemical performance test results of the sodium ion battery electrode prepared in Application Example 3 are shown. DETAILED DESCRIPTION

[0034] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0035] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] In the following examples, the room temperature refers to 25±2°C.

[0040] In the following examples, the coal-based material is bituminous coal, anthracite, lignite or petroleum coke. In the following examples, bituminous coal is used as an example to prepare the Mn-BiOCl-coal-based hard carbon composite material.

[0041] In the following examples, the carbon precursor material is bituminous coal;

[0042] In the following embodiment, a method for preparing a Mn-BiOCl-coal-based hard carbon composite material comprises the following steps:

[0043] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60°C for 6-12h, centrifuged and dried;

[0044] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1200-1600°C, and calcining at high temperature for 2-4h to obtain a coal-based hard carbon material;

[0045] 3) According to Bi(NO 3 ) 3 ·5H 2 The molar volume of O, NaCl, manganese salt and distilled water is 3mmol:3mmol:(3-6)mmol:70mL. 3 ) 3 ·5H 2 O, NaCl and manganese salt were added into distilled water and stirred for 30 min to obtain a mixed solution;

[0046] Wherein, the manganese salt includes: MnCl 2 , Mn 2 CO 3 , C 4 H 6 MnO 4 ·4H 2 O、MnSO 4 and Mn(NO 3 ) 2 ;

[0047] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: (0.1-0.3) g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0048] 5) The coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace at a mass ratio of (1-10) : 1, and calcined at 500°C for 1-12h. After cooling to room temperature, the mixture is crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0049] In the following embodiments, a preparation of a sodium ion battery electrode comprises the following steps:

[0050] 1) Sieving the Mn-BiOCl-coal-based hard carbon composite material using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0051] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0052] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0053] Example 1

[0054] A Mn-BiOCl-coal-based hard carbon composite material

[0055] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0056] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1200°C, and calcining at high temperature for 2h to obtain a coal-based hard carbon material;

[0057] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, MnCl 2 and distilled water in a molar volume of 3mmol:3mmol:3mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and MnCl 2 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0058] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.1 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0059] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 2:1, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0060] Application Example 1

[0061] Preparation of a sodium ion battery electrode

[0062] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 1 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0063] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0064] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0065] The electrochemical performance of the sodium ion battery electrode prepared in Example 1 was tested. The test results are as follows Figure 1 As shown;

[0066] Depend on Figure 1 It can be seen that the sodium ion battery electrode prepared in Application Example 1 is -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 743.3mAh g -1 、394.2mAh g -1 and 361.7mAh g -1 , the first-cycle Coulomb efficiency is 55.3%.

[0067] Example 2

[0068] A Mn-BiOCl-coal-based hard carbon composite material

[0069] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0070] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0071] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, MnCl 2 and distilled water in a molar volume of 3mmol:3mmol:4.5mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and MnCl 2 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0072] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0073] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:1, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0074] Application Example 2

[0075] Preparation of a sodium ion battery electrode

[0076] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 2 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0077] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0078] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0079] The electrochemical performance of the sodium ion battery electrode prepared in Example 2 was tested. The test results are as follows Figure 2 As shown;

[0080] Depend on Figure 2 It can be seen that the sodium ion battery electrode prepared in Application Example 2 is -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 546.9mAh g -1 , 445.1mAh g -1 and 417.1mAh g -1 , the first-cycle Coulomb efficiency is 79.9%.

[0081] Example 3

[0082] A Mn-BiOCl-coal-based hard carbon composite material

[0083] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0084] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1600°C, and calcining at high temperature for 4 hours to obtain a coal-based hard carbon material;

[0085] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, MnCl 2 and distilled water in a molar volume of 3mmol:3mmol:6mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and MnCl 2 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0086] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.3 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0087] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:2, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0088] Application Example 3

[0089] Preparation of a sodium ion battery electrode

[0090] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 3 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0091] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0092] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0093] The electrochemical performance of the sodium ion battery electrode prepared in Example 3 was tested. The test results are as follows Figure 3 As shown;

[0094] Depend on Figure 3 It can be seen that the sodium ion battery electrode prepared in Application Example 3 is -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 582.2mAh g -1 、326.7mAh g -1 and 298.6mAh g -1 , the first-cycle Coulomb efficiency is 55.6%.

[0095] Example 4

[0096] A Mn-BiOCl-coal-based hard carbon composite material

[0097] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0098] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0099] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, Mn 2 CO 3and distilled water in a molar volume of 3mmol:3mmol:4.5mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and Mn 2 CO 3 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0100] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0101] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:3, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0102] Application Example 4

[0103] Preparation of a sodium ion battery electrode

[0104] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 4 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0105] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0106] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0107] After testing, the sodium ion battery electrode prepared in Application Example 4 has a -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 523.5mAh g -1 , 425.3mAh g -1 and 420.1mAh g -1 , the first-cycle Coulomb efficiency is 81.2%.

[0108] Example 5

[0109] A Mn-BiOCl-coal-based hard carbon composite material

[0110] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0111] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0112] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, C 4 H 6 MnO 4 ·4H 2 The molar volume of O and distilled water is 3mmol:3mmol:4.5mmol:70mL. 3 ) 3 ·5H 2 O, NaCl and C 4 H 6 MnO 4 ·4H 2 O was added into distilled water and stirred for 30 min to obtain a mixed solution;

[0113] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0114] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:4, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0115] Application Example 5

[0116] Preparation of a sodium ion battery electrode

[0117] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 5 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0118] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0119] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0120] After testing, the sodium ion battery electrode prepared in Application Example 5 has a -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 536.5mAh g -1 、438.2mAh g -1 and 417.3mAh g -1 , the first-cycle Coulomb efficiency is 78.3%.

[0121] Example 6

[0122] A Mn-BiOCl-coal-based hard carbon composite material

[0123] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0124] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0125] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, MnSO 4 and distilled water in a molar volume of 3mmol:3mmol:4.5mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and MnSO 4 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0126] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0127] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:5, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0128] Application Example 6

[0129] Preparation of a sodium ion battery electrode

[0130] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 6 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0131] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0132] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0133] After testing, the sodium ion battery electrode prepared in Application Example 6 has a -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 523.5mAh g -1 、425.3mAh g -1 and 420.1mAh g -1 , the first-cycle Coulomb efficiency is 81.2%.

[0134] Example 7

[0135] A Mn-BiOCl-coal-based hard carbon composite material

[0136] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0137] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0138] 3) According to Bi(NO 3 )3 ·5H 2 O, NaCl, Mn (NO 3 ) 2 and distilled water in a molar volume of 3mmol:3mmol:4.5mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and Mn(NO 3 ) 2 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0139] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0140] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:6, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0141] Application Example 7

[0142] Preparation of a sodium ion battery electrode

[0143] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 7 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0144] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0145] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0146] After testing, the sodium ion battery electrode prepared in Application Example 7 has a -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 538.5mAh g -1 、435.3mAh g -1 and 432.3mAh g-1 , the first-cycle Coulomb efficiency is 78.4%.

[0147] Example 8

[0148] A Mn-BiOCl-coal-based hard carbon composite material

[0149] 1) Place the coal-based material in 5 mol·L -1 HCl and 5 mol·L -1 HF mixed solution, stirred at 60 ° C for 8 h, centrifuged and dried;

[0150] 2) placing the coal-based material pretreated in step 1) in a tubular furnace, and under nitrogen protection, controlling the heating rate to be 5°C / min, heating to 700°C, and calcining at high temperature for 3 hours; after the tubular furnace is cooled to room temperature, controlling the heating rate to be 5°C / min, heating to 1400°C, and calcining at high temperature for 3 hours to obtain a coal-based hard carbon material;

[0151] 3) According to Bi(NO 3 ) 3 ·5H 2 O, NaCl, MnCl 2 and distilled water in a molar volume of 3mmol:3mmol:4.5mmol:70mL, Bi(NO 3 ) 3 ·5H 2 O, NaCl and MnCl 2 Add into distilled water and stir for 30 min to obtain a mixed solution;

[0152] 4) adding the mixed solution and the carbon precursor material obtained in step 3) into a hydrothermal reactor according to the mass volume of the mixed solution and the carbon precursor material being 70 mL: 0.2 g, performing a hydrothermal reaction at 160° C. for 16 h, centrifuging, washing, and drying to obtain Mn-BiOCl powder;

[0153] 5) According to the mass ratio of coal-based hard carbon material to Mn-BiOCl powder of 1:7, the coal-based hard carbon material obtained in step 2) and the Mn-BiOCl powder obtained in step 4) are placed in a muffle furnace, calcined at 500°C for 2h, and after cooling to room temperature, crushed to obtain the Mn-BiOCl-coal-based hard carbon composite material.

[0154] Application Example 8

[0155] Preparation of a sodium ion battery electrode

[0156] 1) The Mn-BiOCl-coal-based hard carbon composite material prepared in Example 8 was sieved using a 100-mesh standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size;

[0157] 2) dissolving the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black screened in step 1) in N-methylpyrrolidone according to a mass ratio of Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black of 8:1:1 to obtain an electrode slurry;

[0158] 3) The electrode slurry obtained in step 2) is dried at 60-80° C. for 12 h, and then compacted to obtain the sodium ion battery electrode.

[0159] After testing, the sodium ion battery electrode prepared in Application Example 8 has a -1 The current density of 0.01-1.5V, the discharge capacity of the first three cycles is 536.2mAh g -1 , 445.2mAh g -1 and 442.5mAh g -1 , the first-cycle Coulomb efficiency is 77.9%.

[0160] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that the specific implementation methods of the present invention can still be modified or replaced by equivalents. Any modification or equivalent replacement that does not depart from the spirit and scope of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A method for preparing a Mn-BiOCl-coal-based hard carbon composite material, characterized in that: The following steps are involved: 1) Carbonizing the coal-based material under nitrogen protection to obtain a coal-based hard carbon material; 2) adding Bi(NO3)3·5H2O, NaCl and manganese salt into distilled water and stirring to obtain a mixed solution; 3) mixing the mixed solution obtained in step 2) with the carbon precursor material, and subjecting the mixture to a hydrothermal reaction to obtain Mn-BiOCl powder; 4) The coal-based hard carbon material obtained in step 1) and the Mn-BiOCl powder obtained in step 3) are mixed and calcined to obtain the Mn-BiOCl-coal-based hard carbon composite material.

2. The method for preparing a Mn-BiOCl-coal-based hard carbon composite material according to claim 1, characterized in that: In step 1), the carbonization treatment is specifically as follows: controlling the heating rate to be 5°C / min, heating to 1200-1600°C, and high temperature calcining for 2-4h.

3. The method for preparing a Mn-BiOCl-coal-based hard carbon composite material according to claim 1, characterized in that: In step 2), the manganese salt includes: MnCl2, Mn2CO3, C4H6MnO4·4H2O, MnSO4 and Mn(NO3)2; the molar volume of Bi(NO3)3·5H2O, NaCl, manganese salt and distilled water is 3mmol:3mmol:(3-6)mmol:70mL.

4. The method for preparing a Mn-BiOCl-coal-based hard carbon composite material according to claim 1, characterized in that: In step 3), the mass volume of the mixed solution and the carbon precursor material is 70 mL: (0.1-0.3) g; the hydrothermal reaction is specifically: hydrothermal reaction at 160° C. for 16 hours.

5. The method for preparing a Mn-BiOCl-coal-based hard carbon composite material according to claim 1, characterized in that: In step 4), the mass ratio of the coal-based hard carbon material to the Mn-BiOCl powder is (1-10):1; and the calcination is specifically: calcining at 500° C. for 1-12 hours.

6. A Mn-BiOCl-coal-based hard carbon composite material prepared by the method for preparing a Mn-BiOCl-coal-based hard carbon composite material as claimed in any one of claims 1 to 5.

7. Use of the Mn-BiOCl-coal-based hard carbon composite material as claimed in claim 6 in preparing sodium ion battery electrodes, characterized in that: The following steps are involved: The Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black are dissolved in N-methylpyrrolidone to obtain an electrode slurry, and then the electrode slurry is dried and compacted to obtain the sodium ion battery electrode.

8. The use according to claim 7, characterized in that: Before preparing sodium ion battery electrodes, the Mn-BiOCl-coal-based hard carbon composite material needs to be sieved using a standard sieve to obtain a Mn-BiOCl-coal-based hard carbon composite material with uniform particle size.

9. The use according to claim 7, characterized in that: The mass ratio of the Mn-BiOCl-coal-based hard carbon composite material, PVDF and conductive carbon black is 8:1:1; the drying treatment is specifically: drying treatment at 60-80° C. for 12 hours.